2015
DOI: 10.4236/tel.2015.53049
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Aid’s Effect on Economic Growth, New Results from WAEMU’s Countries

Abstract: This study investigates whether foreign aid (AID) has a significant influence on economic growth in WAEMU's (West African Economic and Monetary Union) countries. We use two (2) types of aid data: aggregate aid and disaggregate aid (aid in education, aid in agriculture, aid in trade policies and regulations and humanitarian aid) to run two (2) different regressions. Both the within-dimension and between-dimension estimators reveal that in the long run, the effect of AID on economic growth is heterogeneous acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Our findings are similar to the results presented by Doucouliagos and Paldam ( 2008 ), Burnside and Dollar ( 2000 ), Fiodendji and Evlo ( 2013 ), Stiglitz ( 2002 ) and Sachs ( 2005 ) who found that, official development assistance contributes to economic growth and poverty reduction. Moreover, contemporary studies on aid effectiveness in the context of Sub-Saharan Africa, the analyzes of Arndt et al ( 2010 ), Dreher and Langlotz ( 2020 ), Aboubacar et al ( 2015 ) and Civelli et al ( 2017 ) come to the same conclusion regarding the positive effect of aid on economic growth. In contrast to our result, which promotes aid effectiveness, Moyo ( 2009 ) and Mbah and Amassoma ( 2014 ) point out that aid has a negative effect on the growth of developing countries in that it encourages mismanagement and only benefits a certain oligarchy in developing countries at the expense of the people and subsequently does not reduce poverty.…”
Section: Resultsmentioning
confidence: 90%
“…Our findings are similar to the results presented by Doucouliagos and Paldam ( 2008 ), Burnside and Dollar ( 2000 ), Fiodendji and Evlo ( 2013 ), Stiglitz ( 2002 ) and Sachs ( 2005 ) who found that, official development assistance contributes to economic growth and poverty reduction. Moreover, contemporary studies on aid effectiveness in the context of Sub-Saharan Africa, the analyzes of Arndt et al ( 2010 ), Dreher and Langlotz ( 2020 ), Aboubacar et al ( 2015 ) and Civelli et al ( 2017 ) come to the same conclusion regarding the positive effect of aid on economic growth. In contrast to our result, which promotes aid effectiveness, Moyo ( 2009 ) and Mbah and Amassoma ( 2014 ) point out that aid has a negative effect on the growth of developing countries in that it encourages mismanagement and only benefits a certain oligarchy in developing countries at the expense of the people and subsequently does not reduce poverty.…”
Section: Resultsmentioning
confidence: 90%
“…(Saleh, Assaf, Ihalanayake, & Lung, 2015) studied the contribution of tourism in GDP for the three countries, Bahrain, Jordan, Saudi Arabia concluding a long-term equilibrium between tourism growth and GDP. (Aboubacar, Xu, & Ousseini, 2015) focused in whether the foreign aid (AID) has an important effect on economic growth in the member countries of the West African Economic and Monetary Union (WAEMU). (Adeleye, Adeteye, & Adewuyi, 2015) studied the effect of international trade on economic growth in Nigeria.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…The aid-growth nexus is debatable not only theoretically, but also empirically. Even though some studies have established positive effect of aid on economic growth (Aboubacar et al, 2015;Lee and Alemu, 2015;Moolio and Kong, 2016;Kitessa, 2018), others find negative (Appiah-- Konadu et al, 2013;Aghoutane and Karim, 2017;Sothan, 2018;Edward and Tumwebaze, 2020;Yahyaoui and Bouchoucha, 2020), and some others find insignificant (Tang and Bundhoo, 2017;Kirikkaleli et al, 2021) aid-growth relationship. The empirical inconclusive findings concerning the relationship between foreign aid and economic growth created skepticism among researchers across the globe.…”
Section: Introductionmentioning
confidence: 99%